The Use of Waste Polymers in Asphalt Mixtures: Bibliometric Analysis and Systematic Review - Jwaida, Zahraa; Dulaimi, Anmar; Md Azree Othuman, Mydin; Özkılıç, Yasin Onuralp; Putra Jaya, Ramadhansyah; Ameen, Arman (MDPI, 2023)
Asphalt is widely employed in road construction due to its durability and ability to withstand heavy traffic. However, the disposal of waste polymers has emerged as a significant environmental concern. Recently, researchers have used polymer waste to modify asphalt pavements as a new approach. This approach aims to improve pavement performance and address the environmental concerns of polymer waste. Researchers have demonstrated that incorporating polymeric waste into asphalt mixtures can lead to performance improvements in asphalt pavements, particularly in mitigating common distresses including permanent deformation and thermal and fatigue cracking. The current comprehensive review aims to summarize the recent knowledge on the usage of waste polymers in asphalt mixtures, encompassing their impact on performance properties and mixture design. The review also addresses different types of waste polymers, their potential benefits, challenges, and future research directions. By analyzing various studies, this review offers insights into the feasibility, effectiveness, and limitations of incorporating waste polymers into asphalt mixtures. Ultimately, this contributes to the advancement of sustainable and environmentally friendly road construction practices.